Impact of the black triangle label on prescribing of new drugs in the United Kingdom: lessons for the United States at a time of deregulation. Issue 11 (31st August 2017) - Horton, Daniel B.; Gerhard, Tobias; Davidow, Amy; Strom, Brian L.
Abstract: Purpose: Newly approved novel drugs in Europe receive a black triangle label to promote pharmacovigilance. With growing momentum for earlier drug approvals and reliance on real‐world evidence, we studied if the black triangle label promotes more judicious prescribing. Methods: We examined whether general practitioners prescribed escitalopram, tadalafil, and vardenafil with a black triangle more cautiously than the same or similar drugs without a black triangle in The Health Improvement Network (UK). We performed interrupted time‐series analyses to estimate changes in new prescription rates and nested case‐control studies to compare characteristics of new users before and after removal of a black triangle. Results: Prescribing rates to the 33 441 new users of these new drugs were highest shortly after initial approval and declined subsequently; there were no increases in rates of new prescriptions after a black triangle's removal (new prescriptions/million/month postlabel: escitalopram −1.5 [95% CI, −1.9 to −1.2]; tadalafil and vardenafil: −0.1 [95% CI, −0.6 to 0.4]). Among drugs in the same class, loss of a patent had more impact on prescribing rates than loss of a black triangle. People who began taking black triangle drugs were less likely to be young or to have multiple comorbidities or recent hospitalization compared with those starting the same drugs after the label's removal. However, these differences generally reflected secular trends seen also in similar, unlabeled medicines. Conclusions: Accelerated drug approvals could cause more uncertainty about drug effectiveness and safety, but specific labeling of newly approved medicines is unlikely to promote more judicious prescribing.